Cases That Respond to Oncothermia Monotherapy. (29th May 2013) - Jeung, Tae Sig; Ma, Sun Young; Yu, Jesang; Lim, Sangwook
Abstract : There is a long history of hyperthermia in oncology, but its wide range acceptance and application are missing even today. A new approach of oncological hyperthermia, oncothermia, looks promising modality of the complementary treatment of advanced malignant cases. Our present paper is targeting this method, trying to answer the question of its feasibility to treat various advanced cases in monotherapy process, as well as its applicability for a long, large number of treatment sessions protocols.